Cancer pain management in Mexico. Issue Volume 12:Issue e2(2022) (30th October 2019) - Lincoln, Sarah Barry; Soto-Perez-de-Celis, Enrique; Chavarri-Guerra, Yanin; Covarrubias-Gomez, Alfredo; Navarro, Mariana; Goss, Paul E
Abstract : Background: Pain control is an essential component of high-quality palliative care. Unfortunately, many low-income and middle-income countries lack an appropriate infrastructure to provide palliative care and suffer from a severe lack of access to opioid analgesics to alleviate pain from various conditions such as cancer. Objectives: We aimed to review the history and current status of cancer pain management in Mexico, a middle-income Latin American country. Our objective was to identify existing barriers to proper, effective opioid use, as well as provide practical recommendations for improvement. Methods: Using a search of EBSCOhost database, PubMed and Google, we found official documents and peer-reviewed articles related to health legislation, opioid consumption, palliative care infrastructure and palliative care training in Mexico. Results: Despite advances in palliative care and access to opioids in Mexico, there are still several barriers that undermine effective pain management, showing a major gap between policy and practice. Although Mexican legislation and guidelines include adequate palliative care and pain control as a right for all patients with cancer, the lack of adequate infrastructure and trained personnel severely hampers the implementation of these policies. Additionally, there are important barriers to prescribing opioids, many of which are related to attempts at reducing the consumption of recreational drugs. Conclusions: Although Mexico has made significant improvements in pain control and palliative care, much needs to be done. Expansion of drug availability, improvement of palliative care training, and constant oversight of regulations and guidelines will help to strengthen Mexico's palliative care services.